Analisis Teknik Permainan Instrumen Flute pada Lagu Concertino for Flute Oleh Hayley Miller Pada pertunjukan Boston Philharmonic Youth Orchestra - Asmon, Shafira Permata Dewi; Widiastuti, Uyuni (JPKS (Jurnal Pendidikan dan Kajian Seni), 2024)
The aim of this research is to: 1) Describe the technical analysis of playing the flute instrument in the song Certino for Flute by Hayley Miller. 2) Describe the interpretation of the song Concertino for Flute by Hayley Miller at the "Boston Philharmonic Youth Orchestra" performance. The theories used in this research are analysis theory, game techniques, interpretation. The method used in this research is a qualitative descriptive method where the sample for this research is the video and sheet music of the Concertino for Flute song. The data collection techniques used are observation, documentation, laboratory work. The research results show: 1) Analysis of flute playing techniques in the song Concertino For Flute by Hayley Miller in this research was carried out by analyzing flute playing techniques, namely: Body Posture, Breathing, Ambition, Fingering, Body Position. 2) The interpretation of the song Concertino For Flute can be seen from the several tempos used (moderato, poco string, Stringendo) and dynamic signs (Forte, Piano, Crescendo, Decrescendo, Meizo Forte), this work wants to show the player's ability to perform the song smoothly deep soul and makes the song very lively.